PEMBELAJARAN PENIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER KEAGAMAAN SISWA DI MI AL ISHLAH SIDOWAYAH BEJI PASURUAN - Azizah, Nurul; Amaliya Nasucha, Juli (ILJ: Islamic Learning Journal, 2024)
The importance of Islamic Religious Education in elementary schools is to foster and nurture students to always understand the values of Islamic teachings as a whole, because in essence Islamic Religious Education aims to increase students' faith, understanding and practice of Islam so that they become students who are faithful and devoted to Allah SWT and have noble character in personal life, community, nation and state. The purpose of Islamic Religious Education is as an identity that contains the values of Islamic teachings that must be applied in the learning process gradually. In line with that, basically the purpose of Islamic Religious Education is aimed at implementing values derived from Islamic teachings as an effort to build student character that is upheld by an educational institution. This research uses descriptive research methodology. Descriptive studies, or data collected using words or pictures rather than numbers. In this case, data is collected using interview transcripts, field notes, photographs, videos, personal letters, memos, and other official records. The results of the PAI teacher's research in improving the religious character of students at MI Al Ishlah Sidowayah Beji Pasuruan both have in common, namely the cultivation of values given in each activity and the role of extracurricular youth mosque which greatly helps the teacher's efforts in improving the religious character of students through various religious activities at MI Al Ishlah Sidowayah Beji Pasuruan.